2004
DOI: 10.1037/1064-1297.12.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco, and Drug Use Disorders and Personality Disorder Symptoms.

Abstract: In a nonclinical sample of 395 young adults, the authors evaluated the relations between major personality traits, Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV; American Psychiatric Association, 1994) personality disorder symptoms, and DSM-IV alcohol use disorders (AUDs). Consistent with previous findings, traits related to disinhibition and negative affectivity were consistently associated with AUDs, as were Cluster B personality disorder symptoms (especially antisocial and borderlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 41 publications
5
68
0
Order By: Relevance
“…In addition, future research is needed which includes both subjective and quantity definition measures of binge drinking, and prescreens trait impulsivity levels to assess the importance of this personality variable on drinking behaviors. Impulsivity describes a large number of behavioral and personality attributes (Trull et al, 2004), and it is possible that the tasks used in the current study did not reflect the aspects of impulsivity associated with alcohol-related behavior. Although existing research suggests that alcohol problems are associated with desire for immediate reward (Bjork et al, 2004;Mitchell et al, 2005), the points used in the study may not have been rated by the participants as important, even though points were associated with winning money.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, future research is needed which includes both subjective and quantity definition measures of binge drinking, and prescreens trait impulsivity levels to assess the importance of this personality variable on drinking behaviors. Impulsivity describes a large number of behavioral and personality attributes (Trull et al, 2004), and it is possible that the tasks used in the current study did not reflect the aspects of impulsivity associated with alcohol-related behavior. Although existing research suggests that alcohol problems are associated with desire for immediate reward (Bjork et al, 2004;Mitchell et al, 2005), the points used in the study may not have been rated by the participants as important, even though points were associated with winning money.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests a link between alcohol consumption and impulsivity. Individuals scoring high on measures of impulsivity and disinhibition are more likely to have an alcohol use disorder (AUD) (Trull et al, 2004). However, although some have described alcohol dependence as a disinhibitory disorder (Noel et al, 2007), the cause and effect status of this relationship is unclear; are impulsive people at greater risk of developing an AUD or does alcohol use trigger impaired control?…”
mentioning
confidence: 99%
“…Its role as a risk factor for drug abuse is based on findings from studies examining drug abuse in relation to impulsivity as a central characteristic of psychopathology and as a dimension of normal personality. It is well recognized that substance abuse disorders have a high comorbidity with antisocial, borderline, histrionic, and externalizing disorders, which are all characterized by under-controlled, impulsive patterns of behavior (e.g., Grekin, Sher, and Wood, 2006;Trull, Waudby, and Sher, 2004). Studies also show that impulsivity, as a dimension of normal personality, is associated with increased risk for alcohol and other drug abuse (Bjork, Hommer, Grant, and Danube, 2004;Dom, D'Haene, Hulstijn, and Sabbe, 2006;Soloff, Lynch, and Moss, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have found that substance abuse disorders have a high comorbidity with personality disorders that are characterized by undercontrolled, disinhibited, and impulsive patterns of behavior, including antisocial, borderline, and histrionic disorders (e.g., Grekin et al, 2006; Moeller et al, 2002; Trull et al, 2004). The relation between impulsivity and substance use has been shown across several classes of drugs, including stimulants, opiates, and alcohol, and across multiple indices of impulsivity, including self-report, behavioral, and neuropsychological measures (for a review, see Verdejo-Garcia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%